2010
DOI: 10.1590/s0103-64402010000100002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of retorque on loosening torque of prosthetic screws under two levels of fit of implant-supported dentures

Abstract: This study evaluated the influence of retorque on loosening torque (Lt) of prosthetic screws in implant-supported dentures with different fit levels. Ten mandibular implant-supported dentures were fabricated and then 20 cast models were then prepared using prosthetic structures to create 2 fit levels: passive fit (Pf) and misfit (Mf). Two tightening techniques were also evaluated: initial torque only (T1); and initial torque and retorque after 10 min (T2). Gold or titanium screws were used, resulting in 4 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0
37

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 13 publications
5
44
0
37
Order By: Relevance
“…The current study showed the maintained torque was lower than the tightening torque for the screws in all groups, which is in agreement with previous studies 3,5,[6][7][8] . This likely occurs due to the phenomenon known as "settling" or "embedment relaxation" 3 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current study showed the maintained torque was lower than the tightening torque for the screws in all groups, which is in agreement with previous studies 3,5,[6][7][8] . This likely occurs due to the phenomenon known as "settling" or "embedment relaxation" 3 .…”
Section: Discussionsupporting
confidence: 93%
“…The higher torque maintenance found for the two holding techniques may be because a longer torque application decreases the irregularities in the threads of the implant and retaining screw, increasing the contact between them during the preload and consequently, decreasing the settling effect. The retorque application after the settling effect may act to regain preload and increase the contact area between the threads; for this reason, several researchers have advocated that retorque application 10 min after the initial application should be performed routinely during abutment-implant connections 3,5,6 . The current study showed that this technique was most effective when associated with holding the torque for 20 s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been observed that holding the torque meter for a period of time during the tightening of the screws could provide an elongation of the screw and increased pre-load1819.…”
Section: Discussionmentioning
confidence: 99%
“…A misfit in the denture frameworks can cause many complications, including biological effects such as inflammation of the surrounding tissue, pain, bone deformation and remodeling, continual resorption or even the loss of osseointegration (5). Technical complications include abutment fractures, screw loosening or fractures, and fracture of the framework (6,7).…”
Section: Introductionmentioning
confidence: 99%